The pharmacist and the challenges of self-medication for the elderly in Brazil - Santos, Fabiola Pereira dos; Cardoso, Tiago Souto; Queiroz, Fellipe José Gomes (Revista Coleta Científica, 2021)
Theme: Self-medication in times of pandemic. Problem: What are the reasons that induce the elderly in Brazil to self-medicate? Hypothesis: The elderly are the population with the highest rate of self-medication as a constant practice, this is due to many factors, including the difficulty of constant medical monitoring. Objectives: To describe the main reasons that lead the elderly to self-medicate in Brazil. Justification: It is clear that the proportionality of the growth of the elderly population in Brazil has not been followed by research and epidemiological studies, especially with statistics on the consumption of over-the-counter medicines in this age group. Methodology: This is a literature review. Results. Self-medication is a phenomenon known to be harmful to health. Thus, the indication of medication for the elderly requires special attention from the pharmacist, with professional assistance aimed at reducing the damage caused by the indiscriminate and improper use of non-prescription medication.